Public evaluations of the South African Presidents - Felton, Jamy (Department of Political Studies, 2017)
This study investigates the nature of public evaluations of the presidents of South Africa over time. It consists of two statistically explorative components; a descriptive analysis which looks at the nature of Presidential Approval, and a multivariate analysis which tests competing hypothesis. Using IDASA and Afrobarometer data from 1997, 2000, 2002, 2004, 2006, 2008, 2011 and 2015, this thesis tests an Identity hypothesis, a Performance Evaluation hypothesis and a Cognitive Awareness hypothesis to determine which factors predict approval levels of the president. Findings indicate that South Africans are more likely to make use of low-information reasoning when ascribing support than to use their cognitive awareness of current affairs. There is an indication that South Africans who share an identity with the president are more likely to approve of the president - especially in recent years. However, South Africans are rational people who are more likely to base their approval of the president on how the government performs and how they perceive the economy.